PRAGMATISM AS A LINGUISTIC DISCIPLINE AND ITS PLACE AMONG OTHER SCIENCES - Shaxzodaxon Sanakulova Sheraliyevna; Suleymanova Nargiza Mardonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Until the mid-20th century, the term "pragmatics" was employed by different fields of research (such as semiotics, philosophy, sociology, psychology), which made the content of the term very wide and ambiguous. Due to the emergence and development of linguistically oriented pragmatics, it became necessary to define the place of pragmatics in relation to linguistics and to determine the range of tasks it serves to accomplish. There are three ways to interpret the relationship between pragmatics and linguistics: 1) pragmatics is a separate discipline closely related to linguistics; 2) pragmatics is a branch of linguistics; 3) pragmatics belongs to a certain branch of linguistics. The article discusses these three possibilities with reference to the existing literature. Pragmatics is postulated as a discipline of its own, if it is developed as a cross-disciplinary theoretical approach. When considered among other branches of linguistics, it is referred to as pragmalinguistics or linguistic pragmatics. Nowadays, this is the most widespread point of view found in many linguistic dictionaries and handbooks. Those who view pragmatics as part of a certain branch of linguistics, usually attribute it to text linguistics or semantics. In conclusion, the author proposes another interpretation: in addition to core linguistics, applied linguistics, interdisciplinary linguistics and other possible subdivisions, it is expedient to distinguish communicational linguistics. Pragmatics makes part of it, alongside with phonetics.